Using Problem-Based Learning-Autograph to improve the critical thinking-numeracy ability: a mixed method study in an Integral Calculus course - Zetriuslita; Ariawan, Rezi; Suripah; Yulianti, Ana; Hidayat, Riyan (Universitepark, 2025)
Background/purpose. This study aims to improve students' mathematical critical-numeracy thinking skills by applying the Problem-Based Learning-Autograph model. Materials/methods. This study used a mixed method with a sequential explanatory strategy, and the research design is a one-group pretest-posttest design. The population included students who take the Integral Calculus course, and the sampling is a total sampling. The research instruments were mathematical critical thinking-numeracy test instruments and non-test instruments in the form of interview instruments. Data analysis was conducted using descriptive statistics and inferential statistics. Because the pre-test data were not normally distributed, a non-parametric analysis was conducted, namely the Wilcoxon Signed-Rank Test. The results of in-depth interviews were used to triangulate the data. Results. From the Wilcoxon test, it is obtained that Asymp Sig (2-tailed) = 0.000 < α, Ho is rejected or H1 is accepted. It is concluded that there is a significant difference in students' mathematical critical thinking-numeracy skills before and after learning with the Problem-Based Learning-Autograph model. It means that the results of data analysis showed that there was an increase in students' mathematical critical thinking-numeracy skills after learning using the Problem-Based Learning-Autograph model. The students felt more engaged and motivated in the learning process, which contributed to the improvement of their skills. Conclusion. There is an increase in students' mathematical critical thinking-numeracy skills after learning by using PBL-Autograph learning in the course of Calculus Integral, and students are motivated in the learning process.